LINE × TESTER ANALYSIS USING CMS SYSTEM IN RICE (ORYZA SATIVA L.) - I. S. THAKARE; A. L. PATEL; A. M. MEHTA (The Bioscan, 2013)
Eighteen rice (Oryza sativa L.) genotypes consisting three CMS lines were crossed in a line × tester mating design. The 45F1’s and their parents were evaluated with three standard checks in a randomized complete block design with three replications at the Main Rice Research Station, Anand Agricultural University, Nawagam, Gujarat in kharif 2007. The estimates of gca effects indicated that, among females, IR 68886 A and IR 68897 A and among males IR-44, IR-60, IR-9761, IR-4266-29-4-2-2-2, IR-5638-139-2-2, IR-69701-9-3-1 and IR-71138-49-2-2 were found as good general combiners for grain yield per plant. High sca effects were observed in the crosses, IR 68886 A × IR-44, IR 68897 A × IET-15554, IR 68897 A × IR–56455-206-2, IR 68902 A × IR-4266-29-4-2-2-2 and IR 68897 A × IR–62161-184-3-1-3-2. They were found to be the best combinations for grain yield per plant and quality traits. The preponderance of non-additive type of gene actions clearly indicated that selection of superior plants should be use for further improvement.